Technological advancement and accounting information relevance among small and medium enterprises in Nigeria - ADEGBAYIBI, Adesanmi Timothy (Edelweiss Applied Science and Technology, 2025)
The study assessed the effect of technological advancement and accounting information relevance among Small and Medium Enterprises (SMEs) in Nigeria, specifically examining effect of cloud computing, blockchain technology, and artificial intelligence on the relevance of accounting information among SMEs in Nigeria. The study employed survey research design and used partial least squares structural equation modelling. The population comprised 7,889 registered SMEs in Ondo State, Nigeria, as recorded by SMEDAN in 2023. The sample size was 380 SMEs, determined using the Taro Yamane formula. This study revealed that blockchain technology enhances the relevance of accounting information, while artificial intelligence reduces it. Additionally, the results indicated that cloud computing has a significant positive impact on both blockchain technology and artificial intelligence. The study concludes that technological advancement, particularly cloud accounting, significantly impacts the relevance of accounting information. The study has practical implications for managers to integrate technological advancements into their financial operations to enhance efficiency and ensure the relevance of information for end users, meets stakeholders’ needs and supports sound economic decision-making. Also, companies should adopt blockchain technology to improve the quality of financial reports, stabilize the company, and provide valuable information for economic decision-making.